Optimizing Visual Communication: An Interdisciplinary Approach of Semiotics and Management to Digital Presentation Platforms - Kusuma Putri, Dyah Ayu Anta; Pratama, Alun (CV. Publikasi Indonesia, 2025)
In the digital era, presentation platforms such as Prezi, Canva, and PowerPoint have become fundamental instruments in professional and educational communication. However, their utilization is often confined to functional aspects, lacking a profound understanding of how each platform uniquely shapes and communicates meaning. This paper, written from an interdisciplinary perspective of linguistics (semiotics) and management, aims to comparatively analyze the semiotic affordances of these three platforms and explore their managerial implications for strategic communication decision-making. Employing a framework of social semiotics and multimodality , we dissect how each platform facilitates meaning construction through visual, textual, spatial, gestural, and auditory semiotic modes. The analysis reveals fundamental differences: Prezi excels in spatial and gestural semiotics, making it ideal for non-linear narratives and concept mapping. Canva stands out in visual and textual semiotics, facilitating the creation of aesthetic and communicative multimodal texts. Meanwhile, PowerPoint, with its linear structure, offers flexibility in audio integration and the delivery of structured information. From a management standpoint, this understanding is crucial. The choice of a platform is not merely a technical selection but a strategic decision that impacts persuasion, audience engagement, and message clarity. This analysis asserts that an awareness of the semiotic potential of a digital tool empowers educators, managers, and professionals to select the most appropriate instrument for their communication goals, thereby enhancing the processes of learning and meaning construction in the digital age